PENGARUH KEPEMIMPINAN ORGANISASIONAL DAN MODERATOR TURBULENSI LINGKUNGAN TERHADAP RETENSI KARYAWAN (KASUS PADA PERUSAHAAN-PERUSAHAAN PUBLIK DI JABODETABEK) - Singmin Johanes Lo; Musa Hubeis; Parulian Hutagaol; Aji Hermawan (School of Business, Bogor Agricultural University (SB-IPB), 2011)
The purpose of this research was to examine the influence of organizational leadership behaviors and environmental turbulence moderator on employee retention. A survey was used to collect data from various publicly listed companies in the Greater Area of Jakarta. The survey measured the perceptions on organizational leadership behaviors and business environmental turbulence. The survey questionnaire on organizational leadership behaviors was from Yukl’s model and the questionnaire on environmental turbulence was from Ansoff’s model. Fifty two questionnaires were collected by using purposive sampling technique. The Moderated Multiple Linear Regression Analysis was used for analyzing the data. The results showed that the Relations Oriented Behaviors was found to have significant positive relationship with the Employee Retention. The Environmental Turbulence significantly moderated the Relations Oriented Behaviors and affected the Employee Retention positively. Keywords: Organizational Leadership, Environmental Turbulence, Employee Retention